Dynamic Tracking of Acute Ischemic Tissue Fates Using Improved Unsupervised ISODATA Analysis of High-Resolution Quantitative Perfusion and Diffusion Data - Shen, Qiang (2004)
High-resolution (200 × 200 × 1,500 (μm(3)) imaging was performed to derive quantitative cerebral blood flow (CBF) and apparent diffusion coefficient (ADC) maps in stroke rats (permanent occlusion) every 30 minutes up to 3 hours after occlusion onset, followed by histology at 24 hours. An improved automated iterative-self-organizing-data-analysis-algorithm (ISODATA) was developed to dynamically track ischemic tissue fate on a pixel-by-pixel basis during the acute phase. ISODATA-resolved clusters were overlaid on the CBF-ADC scatterplots and image spaces. Tissue volume ADC, and CBF of each ISODATA cluster were derived. In contrast to the single-cluster normal left hemisphere (ADC = 0.74 ± 0.02 × 10(−3) mm(2)/s, CBF = 1.36 ± 0.22 mL g(−1)min(−1), mean ± SD, n = 8), the right ischemic hemisphere exhibited three ISODATA clusters, namely: “normal” (normal ADC and CBF), “ischemic core” (low CBF and ADC), and at-risk “perfusion-diffusion mismatch” (low CBF but normal ADC). At 180 minutes, the mismatch disappeared in five rats (Group I, 180-minute “core” lesion volume = 255 ± 62 mm(3) and 24-hour infarct volume = 253 ± 55 mm(3), P > 0.05), while a substantial mismatch persisted in three rats (Group II, 180-minute CBF-abnormal volume = 198 ± 7 mm(3) and 24-hour infarct volume 148 ± 18 mm(3), P < 0.05). The CBF (0.3 ± 0.09 mL g(−1)min(−1)) of the “persistent mismatch” (Group II, 0.3 ± 0.09 mL g(−1) min(−1)) was above the CBF viability threshold (0.2 to 0.3 mL g(−1)min(−1)) throughout and its ADC (0.70 ± 0.03 × 10(−3) mm(2)/s) did not decrease as ischemia progressed. In contrast, the CBF (0.08 ± 0.03 mL g(−1)min(−1)) of the analogous brain region in Group I was below the CBF viability threshold, and its ADC gradually decreased from 0.63 ± 0.05 to 0.43 ± 0.03 × 10(−3) mm(2)/s (ADC viability threshold = 0.53 ± 0.02 × 10(−3) mm(2)/s). The modified ISODATA analysis of the ADC and CBF tissue characteristics during the acute phase could provide a useful and unbiased means to characterize and predict tissue fates in ischemic brain injury and to monitor therapeutic intervention.